PENGEMBANGAN MEDIA TOUR THE ZOO PADA PEMBELAJARAN IPA HARMONI DALAM EKOSISTEM KELAS V SD - Maretha, Dhea; Ida Suryani; Patricia H.M. Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
There are still many teachers who use the lecture method and lack of interesting learning media so that learning becomes monotonous and boring. This type of research and development of learning media uses the Research and Development method or (R&D) with the ADDIE development model which has five stages, namely analysis, design, development, implementation, and evaluation. Questionnaires consist of media validation questionnaires, material validation, language validation, teacher responses, and student responses. The subjects in this study involved fifth grade students of SDN 13 Rambutan. Based on the results of the development and research conducted on the development of Tour The Zoo media on learning science harmony in the ecosystem of grade V SD, the validation results obtained a percentage of 84.8% for the total validation of media, material and language. For practicality, it obtained a percentage of 96% which was obtained from the value obtained from the teacher response questionnaire instrument, one to one (one-on-one trial) then small group (small group trial). Based on the data, the results show that Tour The Zoo media is categorized as very valid and very practical to use in the learning process of science in grade V SD on the material of harmony in the ecosystem. This learning media can be applied by teachers to help students learn.